A Sphingosine-1-Phosphate Lyase Mutation Associated With Congenital Nephrotic Syndrome and Multiple Endocrinopathy - Maharaj, Avinaash; Theodorou, Demetria; Banerjee, Indraneel (Indi); Metherell, Louise A.; Prasad, Rathi; Wallace, Dean (Frontiers in Pediatrics, 2020)
Background: Loss of function mutations in SGPL1 are associated with Sphingosine-1-phosphate lyase insufficiency syndrome, comprising steroid resistant nephrotic syndrome and primary adrenal insufficiency (PAI) in the majority of cases. SGPL1 encodes sphingosine-1-phosphate lyase (SGPL1) which is a major modulator of sphingolipid signalling. Case presentation: A Pakistani male infant presented at five months of age with failure to thrive, nephrotic syndrome, primary adrenal insufficiency, hypothyroidism and hypogonadism. Other systemic manifestations included persistent lymphopenia, ichthyosis and motor developmental delay. Aged 9 months, he progressed rapidly into end stage oligo-anuric renal failure and subsequently died. Sanger sequencing of the entire coding region of SGPL1 revealed the novel association of a rare homozygous mutation (chr10:72619152, c.511A>G, p.N171D; MAF - 1.701e-05) with the condition. Protein expression of the p.N171D mutant was markedly reduced compared to SGPL1 wild type when overexpressed in an SGPL1 knockout cell line, and associated with a severe clinical phenotype. Conclusions: The case further highlights the emerging phenotype of patients with loss-of-function SGPL1 mutations. Whilst nephrotic syndrome is a recognised feature of other disorders of sphingolipid metabolism, sphingosine-1-phosphate lyase insufficiency syndrome is unique amongst sphingolipidoses in presenting with multiple endocrinopathies. Given the multi-systemic and progressive nature of this form of PAI/ nephrotic syndrome, a genetic diagnosis is crucial for optimal management and appropriate screening for comorbidities in these patients.